2021
DOI: 10.1177/0306624x20986534
|View full text |Cite
|
Sign up to set email alerts
|

Battered Immigrant Women and the Police: A Canadian Perspective

Abstract: Since the 1970s, the state response to intimate partner violence (IPV) has increasingly become one of criminalization—particularly police intervention. Little is known, however, about marginalized women’s experiences with the police within a context of intimate partner violence in Canada. Drawing on interviews with 90 battered immigrant women, this study examines which women contact the police, why some do not, and what characterizes their experiences when the police are involved in an IPV incident. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Of the 31 studies selected, 25 did not report a comparison group for insecure immigration status [ 22 , 63 , 64 , 66 69 , 70 , 71 , 73 77 , 79 , 80 , 83 91 ]. Thirteen of the included reports included only female participants [ 63 , 66 , 70 , 72 , 73 , 78 , 80 82 , 86 , 87 , 92 , 93 ]. One study was exclusively male [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 31 studies selected, 25 did not report a comparison group for insecure immigration status [ 22 , 63 , 64 , 66 69 , 70 , 71 , 73 77 , 79 , 80 , 83 91 ]. Thirteen of the included reports included only female participants [ 63 , 66 , 70 , 72 , 73 , 78 , 80 82 , 86 , 87 , 92 , 93 ]. One study was exclusively male [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only three studies reported gender as a non-binary category [ 69 , 85 , 91 ]. While Couture-Carron et al [ 92 ] met the inclusion criteria, because experience of violence was part of the inclusion criteria for that study, and all participants were in insecure status, it could not be included in the prevalence estimation.…”
Section: Resultsmentioning
confidence: 99%
“…Such perceptions have vast implications for public health. First, when people are too afraid to call police for help, this increases the risk of victimization and even death [ 58 , 59 ]. Second, when people are unwilling to cooperate with police, this limits crime detection, control, and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…However, the support received from these sources might not be adequate, thereby delaying the separation process or leading victims to return to their ex-partner. For example, survivors’ perceptions of police support can play a role in their decision to stay or leave ( Johnson, 2007 ; Nnawulezi et al, 2021 ; Couture-Carron et al, 2022 ). Moreover, professionals (e.g., psychologists, gynaecologists, and general practitioners) might hold stigmatising attitudes toward DA victims ( Garimella et al, 2000 ; Peltzer et al, 2003 ; Baraldi et al, 2013 ).…”
Section: Factors Influencing the Separationmentioning
confidence: 99%